2022
DOI: 10.1186/s13059-022-02616-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 3D genome architecture of cotton fiber reveals subgenome-coordinated chromatin topology for 4-staged single-cell differentiation

Abstract: Background Despite remarkable advances in our knowledge of epigenetically mediated transcriptional programming of cell differentiation in plants, little is known about chromatin topology and its functional implications in this process. Results To interrogate its significance, we establish the dynamic three-dimensional (3D) genome architecture of the allotetraploid cotton fiber, representing a typical single cell undergoing staged development in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 119 publications
(96 reference statements)
0
24
0
Order By: Relevance
“…The results from this study, showing preponderance of triad-specific bias trends across developmental stages, suggest the spatial and temporal variability of HEB, leading to different bias trends through developmental stages, in addition to stress responsive patterns. In allopolyploid cotton, a study analysing the fiber development, revealed the changes in chromatin architecture in the different developmental stages and their influence on gene regulatory networks (GRNs) leading to HEB 55 . This highlights the potential role of dynamic variation in 3D chromatin architecture in bringing about spatiotemporal differences in HEB.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study, showing preponderance of triad-specific bias trends across developmental stages, suggest the spatial and temporal variability of HEB, leading to different bias trends through developmental stages, in addition to stress responsive patterns. In allopolyploid cotton, a study analysing the fiber development, revealed the changes in chromatin architecture in the different developmental stages and their influence on gene regulatory networks (GRNs) leading to HEB 55 . This highlights the potential role of dynamic variation in 3D chromatin architecture in bringing about spatiotemporal differences in HEB.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in rice leaf mesophyll tissues, the count of trans interactions was higher than that of cis interactions. In a study focusing on cotton fibers, it was also observed that the number of trans interactions exceeded the number of cis interactions specifically at 20 days post‐anthesis (Pei et al., 2022). These findings indicate significant variations in the ratio of cis / trans interactions across different samples.…”
Section: Discussionmentioning
confidence: 99%
“…Upon perceiving environmental changes and developmental signals, both global and local chromatin rearrangements may occur, accompanied by changes in the gene transcription levels (Probst & Mittelsten, 2015; Rosa et al., 2013). With the advent of new techniques, an increasing number of studies have been conducted on chromatin conformation (Pei et al., 2022; Yuan et al., 2022; Zhang, Pandey, et al., 2021). Microimaging techniques based on fluorescence in situ hybridization, such as fluorescence labeling imaging and ChromEMT tomography (Cremer & Cremer, 2001; Ou et al., 2017), and high‐throughput sequencing techniques based on chromatin conformation capture and chromatin‐interaction capture, such as high‐throughput chromosome conformation capture (Hi‐C) and ChIA‐PET (Fullwood et al., 2009; Lieberman‐Aiden et al., 2009), are the two main methods used to study the three‐dimensional (3D) structure of genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The trees were beautified and annotated using the iTOL online tool (https://itol.embl.de/). Collection of published RNA‐seq data from multiple tissues of G. hirsutum TM‐1 (Texas Marker‐1) and calculation of gene expression levels used the same pipeline as previously reported (Pei et al., 2022), followed by visualization of a clustered heatmap using R package pheatmap (version 1.0.12).…”
Section: Methodsmentioning
confidence: 99%